1993
DOI: 10.1111/j.1398-9995.1993.tb00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to Parietaria officinalis pollen in newcomers to the area with the plant

Abstract: Hypersensitivity to Parietaria officinalis (wall pellitory) pollen and other environmental allergens was studied in pollinosis patients allergic to P. officinalis pollen who were born in areas without P. officinalis and later moved to the city of Split, where P. officinalis is responsible for some 65% of pollinosis cases. Highly significant positive correlations were found for both the intensity of skin test reaction and concentration of specific serum IgE with the length of residence in the area. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Pollens appear seasonally and are reflected in the symptoms of patients with SR living in temperate climates. Recent studies have shown that grass pollen in Turkey [4,5,6,7,8], birch and grass pollens in northern Europe [17,18,19,20,21], ragweed pollen in America [22], and mugwort and olive pollens in the Mediterranean area [23,24,25,26,27] are the most common and important allergens of these regions. Since Turkey is located between Europe and Asia like a bridge, all four seasons can be present in different regions of the country at the same time of the year.…”
Section: Discussionmentioning
confidence: 99%
“…Pollens appear seasonally and are reflected in the symptoms of patients with SR living in temperate climates. Recent studies have shown that grass pollen in Turkey [4,5,6,7,8], birch and grass pollens in northern Europe [17,18,19,20,21], ragweed pollen in America [22], and mugwort and olive pollens in the Mediterranean area [23,24,25,26,27] are the most common and important allergens of these regions. Since Turkey is located between Europe and Asia like a bridge, all four seasons can be present in different regions of the country at the same time of the year.…”
Section: Discussionmentioning
confidence: 99%
“…The grasses pollinate at the end of spring and beginning of summer, but, in some places such as Southern California or Florida, they are spread throughout the year. Bermuda grass (Cynodon dactylon) and Bahia grass (Paspalum notatum) do not usually cross-react with other grasses (363); • weeds such as the Compositeae plants: mugwort (Artemisia) and ragweed (Ambrosia; 364-366), Parietaria, not only in the Mediterranean area (367)(368)(369)(370)(371)(372)(373), Chenopodium and Salsola in some desert areas (374), weeds such as ragweed flower at the end of summer and beginning of autumn. Parietaria often pollinates over a long period of time (March-November) and is considered as a perennial pollen; • and trees: the birch (Betula), other Betulaceae (375)(376)(377)(378)(379)(380)(381), Oleaceae including the ash (Fraxinus) and olive tree (Olea europea; 382-384), the oak (Quercus), the plane tree (Platanus; 385,386) and Cupressaceae including the cypress tree (Cupressus; 387-392), junipers (Juniperus; 393), thuyas (394), the Japanese cedar (Cryptomeria japonica; 395) and the mountain cedar (Juniperus ashei; 396, 397).…”
Section: Other Mitesmentioning
confidence: 99%
“…Pollens appear seasonally and reflected in the symptoms of seasonal allergic rhinitis in patients living in temperate climates. Recent studies show that grass pollen in Turkey [3][4][5][6][7][8][9][10][11] , birch and grass pollens in northern Europe [16][17][18][19][20] , ragweed pollen in America 21 ; and mugwort and olive pollens in Mediterranean area [22][23][24][25][26] are the most common and important allergens for these regions. This survey shows that the atopy rate and allergen spectra detected by SPT was 90.3 % and the most common sensitizing allergen was grass pollen in patients with SR in Ankara.…”
Section: Discussionmentioning
confidence: 99%